Novel Classes and Evolutionary Turnover of Histone H2B Variants in the Mammalian Germline - Raman, Pravrutha; Rominger, Mary C; Young, Janet M; Molaro, Antoine; Tsukiyama, Toshio; Malik, Harmit S (Molecular biology and evolution, 2022)
Abstract Histones and their posttranslational modifications facilitate diverse chromatin functions in eukaryotes. Core histones (H2A, H2B, H3, and H4) package genomes after DNA replication. In contrast, variant histones promote specialized chromatin functions, including DNA repair, genome stability, and epigenetic inheritance. Previous studies have identified only a few H2B variants in animals; their roles and evolutionary origins remain largely unknown. Here, using phylogenomic analyses, we reveal the presence of five H2B variants broadly present in mammalian genomes. Three of these variants have been previously described: H2B.1, H2B.L (also called subH2B), and H2B.W. In addition, we identify and describe two new variants: H2B.K and H2B.N. Four of these variants originated in mammals, whereas H2B.K arose prior to the last common ancestor of bony vertebrates. We find that though H2B variants are subject to high gene turnover, most are broadly retained in mammals, including humans. Despite an overall signature of purifying selection, H2B variants evolve more rapidly than core H2B with considerable divergence in sequence and length. All five H2B variants are expressed in the germline. H2B.K and H2B.N are predominantly expressed in oocytes, an atypical expression site for mammalian histone variants. Our findings suggest that H2B variants likely encode potentially redundant but vital functions via unusual chromatin packaging or nonchromatin functions in mammalian germline cells. Our discovery of novel histone variants highlights the advantages of comprehensive phylogenomic analyses and provides unique opportunities to study how innovations in chromatin function evolve.